Marie Curie - Rich, Richard; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : Nest Family Entertainment, 2005)
The animated story of Marie Curie, the Polish-born scientist. Her shared research with her husband Pierre gave the world the theory of radioactivity, the discovery of plutonium, and the isolation of radium. She was the first person to receive two Nobel Prizes.
Includes Spanish language track with optional English or Spanish subtitles.
"Premium website accessible through DVD-ROM"--Container.
Includes Resource & Activity Book.
"NEST complete learning system."
Produced & directed by Richard Rich ; executive producer, Jared F. Brown ; screenplay, Brian Nissen ; music, Lex De Azevedo.
DVD ; Dolby digital surround sound.
Keywords: Curie, Marie, -- 1867-1934.; Chemists -- Poland -- Biography; Animated films